Location-Based Marketing - Baray, Jérôme (Wiley-ISTE, 2020)
Location-based Marketing outlines the main concepts, methods and strategies for implementing spatial marketing, also known as geomarketing. With an emphasis on the value of mapping in marketing decision-making, this book demonstrates the importance of a more spatialized view of these decisions, in order to best respond to market realities - whether local or international. The main techniques of geomarketing are presented along with an understanding of the spatial behavior of consumers, both outside the point of sale and in stores. The book further introduces the idea of a "geomarketing mix", which spatializes product innovations, merchandising, pricing and various aspects of promotion. Finally, the book defines what real georetailing comprises and develops the concept of mobile marketing based on geolocation techniques.
Title from content provider